The Profile of Genetic Mutations in Papillary Thyroid Cancer Detected by Whole Exome Sequencing - Yi Fang; Xiao Ma; Jing Zeng; Yanwen Jin; Yong Hu; Jinjing Wang; Ran Liu; Cheng Cao (Cellular Physiology and Biochemistry, 2018)
Background/Aims: The purpose of the study was to investigate the altered driver genes and signal pathways during progression of papillary thyroid cancer (PTC) via next-generation sequencing technology. Methods: The DNA samples for whole exome sequencing (WES) analyses were extracted from 11 PTC tissues and adjacent normal tissues samples. Direct Sanger sequencing was applied to validate the identified mutations. Results: Among the 11 pairs of tissues specimens, 299 single nucleotide variants (SNVs) in 75 genes were identified. The most common pattern of base pair substitutions was T:A>C:G (49.83%), followed by C:G>T:A (18.06%) and C:G>G:C (15.05%). The altered genes were mainly implicated in MAPK (mitogen-activated protein kinase), PPAR (peroxisome proliferator-activated receptors), and p53 signaling pathways. In addition, 12 novel identified driver genes were validated by Sanger sequencing. The mutations of FAM133A, DPCR1, JAK1, C10orf10, EPB41L3, GPRASP1 and IWS1 exhibited in multiple PTC cases. Furthermore, the PTC cases exhibited individual mutational signature, even the same gene might present different mutational status in different cases. Conclusion: Multiple PTC-related somatic mutations and signal pathways are identified via WES and Sanger sequencing methods. The novel identified mutations in genes such as FAM133A, DPCR1, and JAK1 may be potential therapeutic targets for PTC patients.